Hippocampal inflammation is associated with vascular dysfunction in middle aged Non‐Latinx Black APOE‐ε4 carriers. (20th December 2022) - Igwe, Kay C; Lao, Patrick J.; Seblova, Dominika; Swanberg, Kelley; Rivera, Andres M.; Giudicessi, Averi; Tejeda, Emely; Juchem, Christoph; Mayeux, Richard; Manly, Jennifer J; Brickman, Adam M.
Abstract: Background: Neuroinflammation may be associated with global vascular dysfunction and damage. APOE‐ε4, a major genetic risk factor for late onset AD, is expressed in neuroinflammatory cells and may lead to increased pro‐inflammatory cytokine and nitric oxide production in response to injury. We examined the relationship of vascular dysfunction and damage with a magnetic resonance spectroscopy (MRS) marker of neuroinflammation in APOE‐ε4 carriers and non‐carriers. Method: Single proton MRS, pulsed arterial spin labeling (PASL), and T2 fluid attenuated inversion recovery (FLAIR) were collected in a sample of racially/ethnically diverse, middle‐aged adults (n=313, women=67%, age=55±11, years of education=13±3, 72% Latinx/22% Non‐Latinx Black/6% Non‐Latinx White) and used to derive hippocampal Inositol/creatine ratios (Ins/Cr) as a measure of neuroinflammation. Global cerebral blood flow (CBF) was used as a measure of vascular function, and white matter hyperintensity (WMH) volume as a measure of small vessel cerebrovascular damage. APOE genotype was categorized as the presence or absence of at least one ε4 alleles. We estimated general linear models to test main effects and the interaction of APOE‐ε4 and Ins/Cr on WMH or CBF, adjusting for age and stratified by race/ethnicity due to differential prevalence and effects of APOE ε4. Results: In the whole sample, being an ε4 non‐carrier (β=‐12.0 95%CI: [‐24.8, 0.83], p=0.067) and having greater Ins/Cr (β=‐1.1[‐2.2, 0.1], p=0.062) were associated with lower CBF. Within Non‐Latinx Black participants, being an APOE‐ε4 non‐carrier (β=‐40.2[‐73.3, ‐7.1], p=0.02) and having greater Ins/Cr (β=‐3.7[‐73.3, ‐7.1], p=0.007) were associated with lower CBF. The negative association with Ins/Cr was stronger in APOE‐ε4 carriers compared to non‐carriers (β=3.9[0.65, 7.1], p=0.02). No associations of Ins/Cr were observed with WMH. Conclusion: Global vascular dysfunction, but not vascular damage, was related to hippocampal inflammation in APOE‐ε4 carriers among Non‐Latinx Black middle‐aged adults. Neuroinflammation may be linked to vascular brain health which is particularly important for groups with higher APOE‐ε4 prevalence or with greater exposure to social determinants of health that can lead to greater inflammation.